(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
In this article, tasks such as raising the general level of students, increasing interest in the subject, effectively using free time and meeting the needs for knowledge are solved with the help of a foreign language. When defining the goals of the lesson and extracurricular work, firstly, a significant difference between them is assumed, secondly, the characteristics of the types of extracurricular work are taken into account, and finally, thirdly, the practical, educational, developmental goals are fully taken into account.